ANALYSIS OF USER SATISFACTION OF MYSOOLTAN APPLICATION AS SINGLE DIGITAL TOUCH USING PIECES FRAMEWORK - Gabriella Natalie; Evi Maria (JURTEKSI (Jurnal Teknologi dan Sistem Informasi), 2023)
Abstract: This research uses the PIECES framework to analyze user satisfaction with the MySooltan application as a single digital touch for Micro, Small, and Medium Enterprises (MSMEs). The framework was chosen because it has been proven empirically to evaluate information system user satisfaction to see opportunities and improvements in information system development. The sample of this research are users of the MySooltan application, namely MSMEs in Labuan Bajo City. The total sample is 102 respondents. Data was collected using a Google Form questionnaire distributed from October to November 2022 and measured using a Likert scale calculation. The evaluation results found that MSMEs, assisted by Rumah BUMN in Labuan Bajo City, were very satisfied using the MySooltan application during the pandemic. However, PT Telkom still needs to improve the guarantee of confidentiality and protection of user data so that MSMEs can use this application optimally. Keywords: information system; MSMEs; Mysooltan application; PIECES; user satisfaction Abstrak: Tujuan riset ini adalah untuk melakukan analisis kepuasan pengguna aplikasi MySooltan sebagai single digital touch Usaha Mikro, Kecil, dan Menengah (UMKM) menggunakan PIECES framework. Metode ini dipilih karena telah terbukti secara empiris dapat digunakan untuk mengevaluasi kepuasan pengguna sistem informasi untuk melihat peluang dan perbaikan dari sistem informasi yang dikembangkan. Sampel riset ini adalah pengguna aplikasi MySooltan, yaitu UMKM di Kota Labuan Bajo. Total sampel sebanyak 102 responden. Data dikumpulkan menggunakan kuesioner Google Form yang disebar dari bulan Oktober hingga November 2022 dan diukur menggunakan perhitungan skala likert. Hasil evaluasi menemukan secara keseluruhan, UMKM binaan Rumah BUMN di Kota Labuan Bajo sangat puas untuk menggunakan aplikasi MySooltan selama pandemi. Namun demikian, PT Telkom masih perlu meningkatkan jaminan kerahasiaan dan perlindungan data pengguna, agar aplikasi ini dapat digunakan secara optimal. Kata kunci: aplikasi MySooltan; kepuasan pengguna; PIECES; sistem informasi; UMKM